Malaysian corporate taxation (Incorporating 2020 Budget) - Mat Udin, Noraza; Mansor, Muzainah; Derashid, Chek; Ibrahim, Idawati; Abdul Aziz, Saliza; Sulaiman, Aryati Juliana (Universiti Utara Malaysia Press, 2020)
This Malaysian Corporate Taxation book is prepared specifically for students undertaking Advanced Malaysian Taxation course in Universiti Utara Malaysia. The contents of this book cover advanced taxation topics based on Budget 2020. The preparation of this book is based on Income Tax Act 1967, Public Rulings, relevant acts related to direct and indirect taxes as well as other published taxation materials. This book facilitates students’ understanding by using simple explanation of the taxation concepts and illustrations of the related tax computations. This book is structured into 11 chapters, which cover topics in the Advanced Taxation course syllabus. All chapters contain discussion notes and examples of tax computation followed by tutorial questions at the end of the chapters. In closing, we would like to express our gratitude to Allah the Almighty for granting us the opportunity and strength to cooperate in writing this book. It is hoped that this book will benefit the students and other interested parties to understand topics related to Malaysian corporate taxation.